External and Internal Determinants of Inflation: An Application to Libya, 1980-2019 (Journal of Academic Research, 2023)
The study aims to conducts time series data to examine determinants of inflation in Libya’s economy using the econometric methodology O.L.S from 1980 to 2019. The test consists of two models. The first model is the external determinants of inflation and assumes that inflation is related to export value index. The results revealed that inflation is positively related to export value index. The results suggest that export sector has not helped the country in insulating inflation from the impact of oil export. The second model is related inflation to internal determinants and assumes that inflation is related to budget deficit‚ and velocity of money, and import volume index. The results showed that inflation is positively related to budget deficit, that is negatively and insignificantly related to velocity of money‚ and that is positively related to import value index. The results suggest that any increase of budget deficit will increase public depth leading to an increase of imports of commodities and services, a deficit in the balance of payments and a decrease in foreign exchange reserves or leading to an increase in the domestic price level resulting in depreciation of the domestic currency. The results also suggest that inflation is not adjusted by velocity of money, and that Libya¢s economy does not yet produce enough capital and consumer commodities, and that the country is still heavily dependent on the foreign sector for providing capital and consumption commodities for public requires as well as supplying the funds to finance imports.